Propriedades angiogênicas do pólipo nasal no modelo experimental da membrana corioalantóica de embrião de galinha - Goes, Hallyson Andre Nascimento De [UNIFESP] (2019)
Introduction: Nasal polyps are benign, semi-translucent, edematous masses that develop with anomalous growth from the mucosa lining the paranasal cavity, usually originating from the middle meatus mucosa. The participation of angiogenesis in nasal polyposis is fundamental for tissue growth, being proposed based on the positive regulation of proangiogenic factors in polyps, resulting from inflammation, edema or epithelial rupture. Objective: To investigate the potential of nasal polyp tissue to promote or modify angiogenesis. Methods: The effects of the implantation of 12 middle turbinate polyp fragments and 10 intact middle meatus nasal mucosa tissue fragments on the embryo chorioallantoic membrane were studied. The effects on embryonic development were described and correlated with the observed effects on chorioallantoic membrane vessel angiogenesis in 57 embryonic eggs divided into three experimental groups according to the type of tissue implanted: “control”; “Mucosa” and “polyp”. Angiogenesis was assessed by digitized membrane images, by the area and branching index of the medium and large vessels. Embryonic development was evaluated by weight, length and stage according to Hamilton and Hamburger. Results: The implanted tissues differentially modified membrane angiogenesis and embryo development. Nasal polyps, but not mucosal tissues, demonstrated the potential to promote or modify angiogenesis in the embryonated egg of Gallus Domesticus during the studied period (E6-E8). Polyp tissue implants were compatible with the normal development of Gallus Domesticus; mucosal implants induced delays in embryo development. Conclusion: Nasal polyp tissue has a higher angiogenic capacity than normal nasal mucosa tissue, favoring the nutrition and development of polypoid tissue.